Linking Stereotype Congruity to Purchase Behavior Intention: The Roles of Perceived Authenticity and Coffee Shop Preference (Study on Vosco Coffee Consumers in Malang) - Devira, Isma Nadia; Anjaningrum, Widiya Dewi (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Indonesia continues to strengthen its position as one of the world’s most dynamic coffee markets, driven by lifestyle evolution and increasing demand for authentic cafe spaces. Malang, recognized as a hub for education and student culture, has experienced considerable competition amo ng contemporary coffee establishments, particularly Vosco Coffee, which adheres to a lifestyle cafe model. This study aims to examine the influence of stereotype congruity on purchase behavior intention through perceived authenticity, as well as the moderating effect of preference for coffee shops in consumer decision-making. Background Problems: Intense competition and the homogeneity of concepts among coffee shops have caused some coffee shops, including Vosco Coffee, to experience fluctuating sales volumes that fall short of targets. This situation indicates a mismatch between consumer perceptions of the image and expected experience and the reality offered, thus impacting purchase behavior intention. Novelty: This study provides novelty by integrating the concept of stereotype congruity with perceived authenticity and purchase behavior intention within the context of lifestyle cafes, a relationship that has not been extensively examined, particularly in Indonesia’s dynamic coffee market setting. Research Methods: The study used a quantitative methodology, administering online and offline questionnaires to 150 Vosco Coffee drinkers in Malang by accidental sampling. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS version 4.1.1.4. Finding/Results: The findings show that stereotype congruity and perceived authenticity both positively and significantly influence purchase behavior intention, with perceived authenticity also acting as a key mediating factor. Additionally, preference for coffee shops strengthens this relationship, highlighting the strategic importance of aligning brand identity and consumer expectations to enhance purchase behavior intention. Conclusion: This study contributes to the literature on experiential marketing in lifestyle cafes and offers helpful suggestions for coffee shop managers to enhance authentic experiential elements that meet consumer lifestyle perceptions and foster deeper purchase behavior intentions.